Hard-soft-hard layered structure for enhanced mechanical properties in corrugated rolled AZ31 magnesium alloy sheets - Biwu Zhu; Yue Cui; Kang Xu; Xiao Liu; Fan Ye; Wenhui Liu; Pengcheng Guo; Yuanzhi Wu; Xiang Li (Journal of Materials Research and Technology)
Mixed-grains magnesium alloy plates with soft-hard-soft layered structure, fabricated by corrugated plate rolling, exhibit simultaneous improvements in both strength and ductility. The corrugated and flat sides primarily consist of twins, necklace grains and recrystallized grains, while the middle layer is dominated by coarse grains with a small amount of twins and necklace grains. As the average strain rate increases, the twin density and shear band decrease. At a constant average strain rate, from the valley-to-peak, the twin density and the number of coarse grains gradually decrease, while the recrystallization fraction gradually increases. At an average strain rate of 4.3 s−1, the corrugated rolled plates with R = 3 mm achieve an optimal balance of strength (262.6 MPa) and ductility (30.6 %). The corrugated side and flat side contribute to strength through fine grain strengthening and orientation strengthening, while the middle layer with coarse grains provides plasticity. The ordered orientation gradient “sandwich” texture further ensuring ductility. The hard-soft-hard layered structure and the configuration of coarse grains surrounded by fine grains synergistically lead to exceptional mechanical properties.